Inter-comparison of dynamic models for radionuclide transfer to marine biota in a Fukushima accident scenario. (March 2016) - Vives i Batlle, J.; Beresford, N.A.; Beaugelin-Seiller, K.; Bezhenar, R.; Brown, J.; Cheng, J.-J.; Ćujić, M.; Dragović, S.; Duffa, C.; Fiévet, B.; Hosseini, A.; Jung, K.T.; et al.
Abstract: We report an inter-comparison of eight models designed to predict the radiological exposure of radionuclides in marine biota. The models were required to simulate dynamically the uptake and turnover of radionuclides by marine organisms. Model predictions of radionuclide uptake and turnover using kinetic calculations based on biological half-life ( T B1/2 ) and/or more complex metabolic modelling approaches were used to predict activity concentrations and, consequently, dose rates of 90 Sr, 131 I and 137 Cs to fish, crustaceans, macroalgae and molluscs under circumstances where the water concentrations are changing with time. For comparison, the ERICA Tool, a model commonly used in environmental assessment, and which uses equilibrium concentration ratios, was also used. As input to the models we used hydrodynamic forecasts of water and sediment activity concentrations using a simulated scenario reflecting the Fukushima accident releases. Although model variability is important, the intercomparison gives logical results, in that the dynamic models predict consistently a pattern of delayed rise of activity concentration in biota and slow decline instead of the instantaneous equilibrium with the activity concentration in seawater predicted by the ERICA Tool. The differences between ERICA and the dynamic models increase the shorter the T B1/2 becomes; however, there is significant variability between models, underpinned by parameter and methodological differences between them. The need to validate the dynamic models used in this intercomparison has been highlighted, particularly in regards to optimisation of the model biokinetic parameters. Highlights: Comparison of 7 dynamic models for radionuclide transfer in marine biota with the ERICA Tool. 90 Sr, 131 I, 137 Cs in fish, crustaceans, algae and molluscs in a Fukushima scenario. Consistent pattern of delayed uptake and slow turnover by the dynamic models. Differences between ERICA and dynamic models increase with biological half-life. Significant variability between models linked to parameter and methodology differences.